Improved Synthesis of ortho‐Phenylene‐bridged Cyclic Tetrapyrroles and Oxidative Fusion Reactions Toward Substituted Tetraaza[8]circulenes. Issue 6 (22nd January 2021) - Morimoto, Yuki; Chen, Fengkun; Matsuo, Yusuke; Kise, Koki; Tanaka, Takayuki; Osuka, Atsuhiro
Abstract: Hetero[8]circulenes have emerged as novel functionalized heteronanographenes that show various promising functions such as bright fluorescence, charge transporting, and redox reactivities. One of the effective synthetic strategy is the fold‐in type oxidative fusion reaction of ortho ‐phenylene‐bridged cyclic tetrapyrroles, whose construction, however, is not well‐sophisticated in terms of reproducibility and possibility for versatile derivatization. In this paper, a "reverse" coupling strategy has been developed, which enabled synthesis of opp ‐type low symmetric analogues of cyclic tetrapyrroles. Oxidative fusion reaction conditions to afford tetraaza[8]circulenes have also been reinvestigated and improved. Substituent effects of cyclic tetrapyrroles and tetrabenzotetraaza[8]circulenes are studied for solid‐state structures and packing structures, redox potentials, and optical properties. Abstract : An improved method for the synthesis of ortho ‐phenylene‐bridged cyclic tetrapyrrole has been developed. The method enabled to synthesize opposite‐type tetrasubstituted cyclic tetrapyrroles, and the subsequent modified fold‐in type oxidation reaction furnished tetrasubstituted tetraaza[8]circulenes. Their structures, packing, optical and electrochemical properties were comprehensively studied.